The Mediating Role of Marital Infidelity Justification in the Relationship Between Cognitive Flexibility and Marital burnout - Rezaee, Somayeh; Mohammadyfar, Mohammadali; Najafi, Mahmoud (KMAN Counseling & Psychology Nexus, 2026)
Objective: This study aimed to investigate the mediating role of marital infidelity justification in the relationship between cognitive flexibility and marital burnout. Methods: A descriptive-correlational research design with a structural equation modeling (SEM) approach was employed. The statistical population consisted of all married individuals who referred to counseling centers in Districts 3 and 11 of Tehran in 2024. A total of 373 participants were selected using purposive sampling. Data were collected using Pines’ (1996) Marital Burnout Questionnaire, Dennis and VanderWal’s (2010) Cognitive Flexibility Inventory, and Yenisari and Kokdemir’s (2006) Marital Infidelity Justification Scale. Data analysis was performed using SEM. Findings: The results showed that the structural model had a good fit with the collected data. Cognitive flexibility was found to have a significant negative relationship with marital burnout. Additionally, justification of marital infidelity was positively and significantly related to marital burnout. Moreover, justification of infidelity significantly and negatively mediated the relationship between cognitive flexibility and marital burnout. Conclusion: Based on the findings, practical implications can be proposed to improve couple relationships by focusing on the key psychological variables explored in this study.